A real-time integrated fire detection and alarm (FDA) system for network based building automation - Anwar, Farhat; Islam, Rounakul; Hussain, Sabahat; Rashid, Muhammad Mahbubur; Shaikh, Zuhaib (Indian Journal of Science and Technology, 2017)
Objectives: An integrated Fire Detection and Alarm (FDA) systems with building automation was studied, to reduce cost and improve their reliability by preventing false alarm, signal drop and network breakdown. This work proposes an improved framework for FDA system to ensure a robust, intelligent network of FDA control panels in real-time. Methods/Analysis: In this work, the shortest path algorithm was chosen for series of buildings connected by a fiber-optic network. The framework shares information through the algorithm and communicates with each fire alarm panels connected in peer to peer configuration to declare the network state in every second using network address. The declaration from every building connected to the same network appears on Central Control Room (CCR) for real-time monitoring. Findings: The proposed FDA system is different from traditional fire alarm and detection system regarding topology as it manages a group of buildings optimally and efficiently. The single mode fiber-optic connectivity was introduced to reduce signal noises, thus increasing large area coverage and long-term safety. Also, the distributed peer to peer network was proposed to ensure fire survivability where the information is sequentially transmitted. Based on this proposed method a prototype system was designed to validate the performance, where the prototype showed a positive response concerning time consumption and real-time monitoring process than traditional. Improvement: The proposed FDA system got improvement, by consistent network state monitoring framework, fast, reliable connectivity with variable changes possibility and easy maintenance process for increasing robustness and intelligence